Effectiveness of using medical health records as an educational tool in teaching integrated laboratory medicine in phase-II MBBS students - Sreedharan, Sily; Thandyaparambil, Deeshma; Kannadas, Shima; Kunnuvarth, Rajeevan (International Journal of Research in Medical Sciences, 2026)
Background: Undergraduate medical students develop technical proficiency in laboratory medicine but frequently lack understanding of clinical significance. This knowledge gap impairs their integrated approach to data interpretation and makes analytical exercises challenging, highlighting the need for improved teaching methodologies. Methods: A comparative study of 106 medical students randomly divided into control and intervention groups was conducted. The intervention group received instruction using duplicated medical health records, while the control group was taught using traditional case-based learning. Academic performance was assessed through standardized scoring with statistical analysis. A Likert scale questionnaire evaluated intervention group participants' perceptions. Results: No significant difference was found between mean academic scores of control and intervention groups (p=0.567). However, qualitative assessment showed overwhelmingly positive reception, with 98.6% of intervention group students expressing favorable attitudes toward medical health records as effective educational resources for integrated laboratory medicine. Conclusions: Medical health records represent a valuable educational resource for teaching integrated laboratory medicine to undergraduate medical students. However, their effectiveness in improving academic performance remains uncertain. Further studies with larger sample sizes and longer follow-up periods are recommended to strengthen understanding of this educational approach's potential benefits.